Pengaruh Berat Potong dan Harga Pembelian Domba dan Kambing Betina terhadap Gross Margin Jagal di Rumah Potong Hewan Mentik, Kresen, Bantul (The Effects of Slaughter Weight and Purchase Price of Female Sheep and Goats on the Butcher’s Gross Margin at Ment - Wisnu Widiarto; Rini Widiati; I Gede Suparta Budisatria (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
This study was aimed to determine the effect of slaughter weight and purchasing price of female sheep and goats on the butcher’s gross margins at the slaughterhouse of Mentik, Kresen, Bantul. The study was conducted to determinethe production activities of butchers. Sixty heads of local female sheep and goats respectively, were used as samples. The animals were divided into two groups, based on its body weight, namely 10 to 14.99 kg (BP1) and 15 to 20 kg(BP2) of body weight. The data consisted of purchasing price, slaughter weight, variable cost, dressing and non carcass percentages and the butcher’s gross margin. Factorial analysis was used to determine the ratio between spesies andgroups which live weight is best for the production of sheep and female goats. Multiple linear regression analysis was used to determine the effect of slaughter weight and purchase price to production of female sheep and goats, andslaughter weight and variable costs to gross margin of sheep and female goats butchers. The results showed that Bligon female goats of 15-20 kg body weight has the highest value on production and gross margins, it was 9.83 kg and Rp.104,901.50, respectively. The purchasing price and the slaughter weight significantly and positively affecting the production of female local sheep and goats with R2 = 0.718, female goats has better production than sheep. Slaughterweight significantly and positively affecting the gross margin of the butcher. Variable costs significantly and negatively affecting the gross margins of the butcher with R2=0.665. Higher variable cost will reduce the butcher’s gross margin. There were differences in the gross margin of female sheep and goat. The Gross margin of female goats was better than the gross margins of sheep. It can be concluded that local female goat’s production and gross margin was better than sheep.(Key words: Female local sheep and goats, Dressing and non carcass percentages, Production and Gross margin)